Determinants of Bird Species Literacy—Activity/Interest and Specialization Are More Important Than Socio-Demographic Variables - Christoph Randler; Felicitas Heil (Animals, 2021)
Biodiversity is declining, and knowledge about biodiversity declines in a similar way. Previous studies have already addressed predictors of species knowledge. Here, we studied bird species knowledge related to demographics, but also to individual differences in affinity to nature, by including (i) birding specialization and (ii) bird-related activities/interest. Data were collected from July to October 2020 via an online questionnaire, containing demographic data, birding specialization, interest/activity, and images of 28 bird species native to Germany. Participants were adult students, lecturers and administrative staff of the Eberhard Karls University Tübingen. A total of 1967 questionnaires were returned in this study (35.3% male, 53.8% students, 69% had access to a garden). Mean identification score was 16.31 ± 6.38. Thus, participants were able to identify more than half of the species (total species n = 28). Men identified more species than women, garden owners had higher identification scores than non-owners, while hometown size was not significant. A distance to the next forest patch >10 km was related to lower identification scores. Employees scored higher than students. Correlation between species knowledge and birding specialization was high, as was the correlation with bird interest/activity. Higher scores were found in older people. In the linear univariate model, birding specialization and bird interest were the most influential predictors of species knowledge, followed by distance to next forest patch and occupation (student vs employees). Other variables were not significant. We suggest including such measures (interest, attitude, etc.) into further studies and move forward from the urban–rural narrative to more complex analyses of living circumstances.